PENGARUH PROMOSI, KUALITAS PRODUK, DAN KUALITA LAYANAN TERHADAP KEPUASAN PELANGGAN DI FAVE HOTEL AHMAD YANI BEKASI - Melinda Larassati; Rivera Pantro Sukma (LPPM Universitas Asa Indonesia, 2019)
The purpose of this study was to determine the effect of promotion ( ,), product quality ( ) and service quality ( ), on customer satisfaction (Y) at Favehotel Ahmad Yani Bekasi. The instrument has been tested its validity and reliability prior to data collection. This data uses primary data and this study was conducted for 1 month, during May 2018 using the Accidental Sampling technique and giving direct questionnaires to 100 respondents. The data analysis tool used in this study by multiple linear regression with classic assumption test (normality test, multicollinearity test, heteroskedacity test, linearity test). While testing the hypothesis through the F test, the results of the significant by t-test and partial correlation analysis and coefficient of determination ( ). The results of this study indicate that simultaneous promotion, product quality and service quality have a significant effect on customer satisfaction. Promotion and product quality have a negative but significant effect on customer satisfaction, while service quality has a significant positive effect on customer satisfaction.